Contribuição aos métodos de redução de modelos aplicados a sistemas aeroviscoelásticos - Briend, Yvon Pierre Joseph (2017)
The flutter boundary prediction of complex aeroelastic systems is not an easy task. In most cases, it is due to the large number of degrees of freedom of the aeroelastic models. Additionally, if the latter incorporate a control strategy aiming to suppress the flutter phenomenon, such as the use of viscoelastic treatments, the computational cost and time required to predict the flutter speeds of the resulting aeroviscoelastic model is very high, sometimes unfeasible. In this situation, the use o model reduction techniques turns essential. However, the construction of a modal reduction basis for aeroviscoelastic systems is still a challenge, owing to the inherent frequency- and temperature-dependent behavior of the viscoelastic materials. Thus, the main contribution intended for this master thesis is to propose new efficient and accurate reduction methods in frequency and time domains for aeroviscoelastic system. Two structures are under study in order to assess the quality of the methods developed herein, consisting of a three-layered viscoelastic sandwich flat plate and of a system of industrial interest represented by an aeronautic curved panel with stiffeners. Several analysis are performed in order to characterize each method with respect to its efficiency and accuracy. Some parameters are then assessed to quantify the influence of each one over the final result.